A comparative study of judicial supervision on unilateral administrative actions in the legal system of Iran and Algeria - Abdolsaeed Shojaei; davud mohebbi (مطالعات تطبیقی حقوق کشورهای اسلامی)
Judicial supervision is one of the prominent tools of any legal system, so that without paying attention to it, the functioning of that judicial system will not be efficient and effective. Judicial supervision of administration is one of the types of judicial supervision in general in any legal system. The tools of judicial supervision over the administration can be generally divided into two categories: predicting competent judicial authorities and compiling and approving a set of rules and regulations to facilitate supervision. The main topic of this research is to analyze and describe the quality of using these tools in the two legal systems of Iran and Algeria. This research, by using the descriptive-analytical method and analysis of issues including types of unilateral administrative actions, the authorities for handling claims of revocation or annulment of administrative decisions, seeks to answer the question of what are the capacities of the two legal systems of Iran and Algeria in relation to Are there any issues raised?The findings show that considering that in general both follow the dual judicial system, similarities can be seen in the judicial supervision of administrative acts, but considering that in the Algerian legal system, administrative courts in There are public courts in the city, province and the government council in the center, it can be said that the judicial supervision of the unilateral administrative actions of the administration in Algeria is more consistent with the pattern of judicial plurality than in Iran.